MODELLING AND SIMULATION OF 5-DOF ROBOT USING SIMMECHANICS - Fadhel, Essam Z.; Al Juboori, Ameen M.; Hussein, Mustafa T. (Journal of Applied Engineering Science, 2022)
The main idea of this paper is to present the modeling and simulation of an individual 5DOF degrees of freedom robotic arm.  The main axis of the modeling design will be up to the branch of science that makes up Mechatronics. The methods that have been used for the 3D model construction are presented as well as the methods for the simulation. The kinematics problem for the robot system under study is elaborated. Both forward and inverse kinematics is addressed in detail. The CAD model design is also presented. The model parameters are defined for the 3D model and the parameters are used as a base to diverge for the real system. thanks to CAD model translation to SimMechanics model, there is no need for the dynamic equations of motion derivation. The model in SimMechanics is adjusted properly for the trajectory tracking simulation. Several simulations are presented to validate the kinematics solution and the dynamics requirements for the motion. The results presented in the article shows the effectivity of the new softwares in modeling and control of engineering systems.
Keywords: robot arm, manipulator, kinematics, cad model, simmechanics